Didactic strategies and clinical skills developed by veterinary medicine students in a private university in Lima - Peru. - Rondón, Rodrigo (2022)
The objective of the study was to analyze the relationship between the variable's didactic strategies and clinical skills developed by students of Veterinary Medicine at the Universidad Peruana de Ciencias Aplicadas (UPC) in Lima-Peru. The study was observational, descriptive, and correlational. A survey was applied to measure the perception of didactic strategies (teaching perception, cognitive, procedural, and attitudinal), and clinical skills were measured through the application of a questionnaire and a rubric. With Stata software (version 17), the relative and absolute frequency of the student's characteristics and the results of the questionnaire were determined. In addition, Spearman's correlation test was applied to evaluate the correlation between the study variables. A total of 167 students participated, who were between the 2nd and 8th academic cycles. Females represented 76.6% (128) and males 23.4% (39). Most of them were studying between the 2nd and 6th cycle of the course. The average score on the questionnaire and rubric was 13.7 ± 2.8. A total of 76.7% (128) of the students indicated that they agreed or completely agreed with the didactic strategies received. However, the correlation analysis between didactic strategies and clinical skills revealed the existence of a significant linear relationship between the dimensions of teacher perception (indicator: teaching strategies) present in Factor 1 (Rho= -0. 1698; p= 0.028); cognitive (indicator: evaluation with rubrics), present in Factor 4 (Rho= 0.1778; p= 0.0215); and attitudinal (indicator: evaluation with rubrics), present in Factor 5 (Rho= 0.1935; p= 0.0122). These results indicate the need to reflect on and review the teaching-learning process developed by the students.